Pengaruh Reward dan Punishment terhadap Kinerja Karyawan PT. Cakra Sanjaya AC - Sartika Novita Sari; Natal Indra; Mega Harti (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study was conducted to determine the effect of reward and punishment on employee performance at PT Cakra Sanjaya AC. In this company, employee performance determines the smooth running of daily operations, including inventory management, customer service, and product delivery. Therefore, the reward and punishment system is used as an effort to increase employee motivation, discipline, and productivity.Despite the implementation of the reward and punishment system, there was a significant difference in employee responses. Employees who received rewards showed a 15% increase in performance, while those who received punishments experienced a decrease in motivation and work enthusiasm. This research uses quantitative methods with descriptive and verification approaches. The sampling technique used was saturated sampling, with a total of 36 employees as respondents.The results showed that reward has a positive and significant effect on employee performance. Punishment also has a positive and significant effect. Simultaneously, reward and punishment together contribute significantly to improving employee performance. Therefore, the application of rewards and punishments in a proportional, targeted, and sustainable manner is very important to create a productive, disciplined, and highly competitive work environment. In addition, companies need to conduct periodic evaluations of the effectiveness of the two systems in order to adjust HR management strategies according to the needs and dynamics of the organization, so that company goals can be achieved optimally.